Hubungan Kelembaban, Kepadatan Hunian dan Kebiasaan Merokok terhadap Kejadian Infeksi Saluran Pernapasan Akut pada Balita di Puskesmas Kecamatan Cipayung - Apriyan, Nur; Adawiyah, Asyifa Robiatul; Agustin, Dinni; Calista, Rachelle Audrey (LPPM Universitas Respati Indonesia, 2025)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality among children in developing countries. In 2023, a total of 30,321 ARI cases were recorded among children aged 1–5 years at the Cipayung Subdistrict Health Center. The main problem in this research area is that there are families who have a smoking habit and this will have an impact on increasing cases of ARI in toddlers every year. This study aims to analyze the relationship between air humidity, housing density, and smoking habits and the incidence of ARI in toddlers in the area in 2024. A cross-sectional study design was used and conducted in November 2024. The population consisted of children aged 1–5 years, with a total sample of 106 respondents selected through cluster random sampling. Data analysis in this study used univariate analysis, bivariate analysis with Chi Square test, multivariate analysis using multiple logistic regression test. The results showed that 57.5% of the toddlers experienced ARI, while 42.5% did not. The Chi-Square test indicated a significant relationship between air humidity (p = 0.043) and smoking habits (p = 0.025) with ARI incidence. However, no significant relationship was found between housing density and ARI. Multiple logistic regression analysis revealed that smoking habits were the most dominant factor associated with ARI incidence. It can be concluded that air humidity and smoking habits are the primary factors influencing the occurrence of ARI in toddlers.